Effectiveness of Akademi Fantasia celebrity endorsements from the eyes of consumers in Klang Valley / Mohd Zulkifli Abdul Razak (Faculty of Business Management, 2007)
Celebrity endorsement has become an important element in advertising and communication management. Therefore, this study will focus on the discussion on Akademi Fantasia celebrity endorsement's effectiveness in Malaysia, Here, the main focus of study is on the perception of the consumer relating their purchasing intention to the Akademi Fantasia celebrity endorsers' attributes, using the TEARS model by Shimp (2003). The objectives are to identify endorser attributes (trustworthiness, expertise, attractiveness, respect and similarity) that are important for the celebrities as perceived important by the consumers, and to identify relationship between consumer's purchasing intentions to respondents' demographic profiles. This research also identifies the relationship between endorser attributes with consumer purchasing intentions. Non-probability sampling is used as sampling method. Knowledgeable respondents that have at least little knowledge on the subject are chosen for the study. Questionnaires handed to the respondents to be answered and collected for further analysis. From the 5 endorser attributes, respect is perceived most important, followed by physical attractiveness, similarity (to the target audience) and trustworthiness. Expertise is perceived least important by respondents. There is no significant difference between purchasing intentions with gender, age group income level of respondents. Respect, physical attractiveness, similarity and trustworthiness have highly significant with moderate positive relationship with consumers' intention to purchase. It is not the researcher's intention to establish facts but rather to identify the consumers' perceptions in order to understand and determine Akademi Fantasia celebrity endorser attributes and its influences to consumer's purchasing intentions. In general, it also increases the understanding of Malaysian consumer regarding the issues of celebrity endorsement as a marketing tool.